Islamic Counseling and Cognitive Psychotherapy for the Treatment of Obsessive-Compulsive Disorder (OCD) in Adolescents - Mujahidah, Shabira; Zahra, Safinah; Hariyadi, Renaya (Journal of Islamic Communication and Counseling, 2025)
Obsessive-Compulsive Disorder (OCD) in adolescents disrupts emotional, academic, and social development, with conventional treatments often lacking sensitivity to spiritual dimensions, particularly in Muslim communities. This study explores the integration of Islamic counseling and cognitive psychotherapy as a holistic and novel intervention for OCD, addressing both clinical symptoms and spiritual well-being. Employing a library research methodology, the study analyzed literature from modern psychology, Islamic teachings, and empirical studies on OCD treatments. The findings emphasize the originality of combining cognitive restructuring with Islamic principles such as tawhid (monotheism) and tazkiyah (self-purification), creating a transformative and culturally sensitive framework for therapy. The proposed intervention encompasses structured spiritual practices (e.g., therapeutic dhikr and Qur'an-based meditation) alongside cognitive techniques, effectively reducing OCD symptoms and enhancing emotional resilience. This integrated approach not only alleviates symptoms but fosters personal growth and spiritual resilience, positioning adolescents as active participants in their healing journey. By bridging gaps between conventional psychotherapy and Islamic values, this study offers a groundbreaking model that significantly contributes to contemporary mental health interventions within Muslim contexts.